CEUS and CT/MRI LI-RADS in Association With Serum Biomarkers for Differentiation of Combined Hepatocellular-Cholangiocarcinoma From Hepatocellular Carcinoma - Zhou, Yan; Yin, Shanshan; Zhao, Lin; Zhang, Xiang; Li, Meng; Ding, Jianmin; Yan, Kun; Jing, Xiang (Frontiers in Oncology, 2022)
Background: Combined Hepatocellular-cholangiocarcinoma (cHCC-CCAs) are with both unambiguously differentiated hepatocellular and biliary components. cHCC-CCAs show various imaging features similar to hepatocellular carcinoma (HCCs) and intrahepatic cholangiocarcinoma (ICCs), which makes the differential diagnosis between them challenging. The accurate diagnosis of cHCC-CCAs is of great importance in selecting treatment methods and performing patient management. Purpose: To investigate the diagnostic efficacy of CEUS and CT/ MRI LI-RADS in association with tumor biomarkers for differentiation of cHCC-CCAs from HCCs. Methods: A total of 54 cHCC-CCAs and 55 HCCs in two centers were retrospectively collected. The diagnostic criteria for cHCC-CCAs if one or more of the following conditions were satisfied: (1) arterial phase hyperenhancement (APHE) on CEUS and LR-M on CT/MRI; (2) LR-5 on both CEUS and CT/MRI with elevated carbohydrate antigen 19-9 (CA19-9); (3) LR-M on both CEUS and CT/MRI with elevated alphafetoprotein (AFP). The sensitivity, specificity, accuracy and area under the receiver operating characteristic curve (AUC) were calculated. Results: The rates of APHE and Rim-APHE on CEUS in cHCC-CCAs were 81.5% and 9.3%, respectively. The rate of early and marked washout on CEUS in cHCC-CCAs were 59.3% and 27.8%, respectively. 64.8% and 25.9% of cHCC-CCAs showed APHE and Rim-APHE on CT/MRI, respectively. 46.3% and 35.2% of cHCC-CCAs showed washout and delay enhancement on CT/MRI, respectively. The kappa value of LI-RADS categories of cHCC-CCAs on CEUS and CT/MRI was 0.319 (P=0.008). The sensitivity, specificity, accuracy and AUC of the aforementioned diagnostic criteria for cHCC-CCAs were 64.8%, 84.4%, 76.1% and 0.746, respectively. Conclusion: The combination of the CEUS and CT/MRI LI-RADS with serum tumor markers shows promising diagnostic performance of cHCC-CCAs.